Предмет: Алгебра,
автор: net12345
Помогите решить 7 класс
Приложения:
Ответы
Автор ответа:
0
Ответ:
В решении.
Объяснение:
1.
а) (х² + х - 1)(х² - х + 1) =
= х⁴ - х³ + х² + х³ - х² + х - х² + х - 1 =
= х⁴ - х² + 2х -1;
б) (2m² + 3m + 1)(-2m² + 3m - 1) =
= -4m⁴ + 6m³ - 2m² - 6m³ + 9m² - 3m - 2m² + 3m - 1 =
= -4m⁴ + 5m² - 1;
2.
a) (c - 1)(c⁴ - c³ + c² - c + 1) =
= c⁵ - c⁴ + c³ - c² + c - c⁴ + c³ - c² + c - 1 =
= c⁵ -2c⁴ + 2c³ -2c² + 2c - 1;
б) (4 - y + у² - у⁵)(1 - у) =
= 4 - y + у² - у⁵ - 4у + у² - у³ + у⁶ = в стандартный вид:
= у⁶ - у⁵ - у³ + 2у² - 5у + 4.
Похожие вопросы
Предмет: Литература,
автор: Zjugaljuma
Предмет: Русский язык,
автор: Аноним
Предмет: Физика,
автор: 1996October
Предмет: Русский язык,
автор: olgaivanchenko1
Предмет: Математика,
автор: venomSpiderMan